Metabolic transition in mycorrhizal tomato roots - Rivero, Javier; Gamir, Jordi; Aroca, Ricardo; Pozo, María J.; Flors, Víctor (Frontiers in Microbiology, 2015)
Beneficial plant-microorganism interactions are widespread in nature. Among them, the symbiosis between plant roots and arbuscular mycorrhizal fungi is of major importance, commonly improving host nutrition and tolerance against environmental and biotic challenges. This manuscript addresses the main metabolic changes that take place in a well established symbiosis between tomato and two common arbuscular mycorrhizal fungi: Rhizophagus irregularis and Funneliformis mosseae. Principal component analysis of metabolites, determined by non-targeted liquid chromatography-mass spectrometry analysis, showed a strong metabolic rearrangement in mycorrhizal roots. There was generally a negative impact of mycorrhizal symbiosis on amino-acid content, mainly on those involved in phenylpropanoids biosynthesis. On the other hand, clusters of compounds, which accumulate more in the mycorrhizal roots than in the non-mycorrhizal roots, contain many intermediaries in amino-acid and sugar metabolism and the oxylipin pathway. The metabolic reprogramming also affected other pathways from the secondary metabolism, mainly phenyl alcohols (lignins and lignans) and vitamins. The results showed that source metabolites of these pathways decreased in mycorrhizal roots, whilst the products derived from -linolenic and amino acids presented higher concentrations in AMF-colonized roots. Mycorrhization, therefore, increased the flux into those pathways. Venn-diagram analysis showed that there are many induced signals shared by both mycorrhizal interactions, pointing to general mycorrhiza-associated changes in the tomato metabolome. Moreover, fungus-specific fingerprints were also found, suggesting that specific molecular alterations may underlie the reported functional diversity of the symbiosis. Since most positively regulated pathways were related to stress response mechanisms, their potential contribution to improved host stress tolerance is discussed.